2021
DOI: 10.3390/su132312951
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Customer Loyalty and Satisfaction in Financial Institutions through Technology Integration: The Roles of Service Quality, Awareness, and Perceptions

Abstract: This study examines the effects of quality of service, product awareness, and perceptions among customers of Islamic financial institutions (IFIs) on customer loyalty through technology integration using customer satisfaction as a mediator. A well-structured, comprehensive questionnaire was developed and data were collected from 203 respondents who were customers of six IFIs in Pakistan and had at least 2 years of experience in dealing confiorm this is correct with these IFIs. A total of 171 accurate responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 91 publications
1
6
0
Order By: Relevance
“…According to previous study, the effect of service quality is positive on customer loyalty, so quality means improved customer loyalty. Similar findings have been shown by Iqbal et al (2021) [15], where service quality and customer loyalty had a positive linear correlation resulting from digitalization. Their findings are also consistent with the findings of this research, where digitalization showed a positive impact on service quality and customer loyalty.…”
Section: -4-verification Of Hypothesis H3supporting
confidence: 86%
See 1 more Smart Citation
“…According to previous study, the effect of service quality is positive on customer loyalty, so quality means improved customer loyalty. Similar findings have been shown by Iqbal et al (2021) [15], where service quality and customer loyalty had a positive linear correlation resulting from digitalization. Their findings are also consistent with the findings of this research, where digitalization showed a positive impact on service quality and customer loyalty.…”
Section: -4-verification Of Hypothesis H3supporting
confidence: 86%
“…Customers' use of products and services, as retaining existing ones has a lower cost than the benefit of gaining new customers. This is considered a motivation for the banking sector to create customer loyalty by providing quality services [15].…”
Section: -Introductionmentioning
confidence: 99%
“…Besides focusing on functional reliability products, business entities also focus on customer quality perception (Vinh et al 2021). A high-quality perception gives a competitive edge to a firm and promotes sustainable relationships with customers (Iqbal et al 2021).…”
Section: Perceived Qualitymentioning
confidence: 99%
“…Text mining is known as one of the best available techniques that can be applied to achieve automatic relation extraction from the published literature and articles. Text mining is being used widely for relation extraction, for instance protein-protein interactions (PPIs) and genedisease relationships, and therefore a corpus [30] is formed specifically for the DDI extraction task [31][32][33]. The DDI extraction task is very similar to relationship extraction studied in depth in the text-mining domain as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%